Mineral Powder Extraction by the Natural Drying of Water from the Public Springs in Borsec - Simona Elena Avram; Denisa Viviana Platon; Lucian Barbu Tudoran; Gheorghe Borodi; Ioan Petean (Applied Sciences)
Borsec is one of the most important mineral water spa resorts in Romania and is also an important mineral water bottling facility. There are several public springs with significant mineral content. The present paper focuses on mineral powder extraction by the drying of water samples collected from springs no. 3, 5, 6, 10, and 11. These springs have a continuous flow being available for everyone who wants to fill a bottle; meanwhile, the rest of the water is discarded into the river. Thus, the dissolved ions such as Ca2+, Mg2+, Na+, and Cl− are wasted. This study aims to investigate the possibility of mineral content extraction as crystalline powder by drying. The dissolved ions’ reaction with carbonic acid generates carbonates which crystallize progressively with the water evaporation. Mineralogical investigation including X-ray diffraction (XRD) and polarized light optical microscopy (POM) reveal that calcite (rhombohedral and pseudo-hexagonal crystals of about 5–25 µm) is the dominant mineral followed by pseudo-dolomite (columnar crystals of about 5–20 µm), aragonite (rhombic and granular crystals of 2.5–15 µm), and natron (prismatic crystals of about 5–20 µm), in addition to small amounts of halite. Scanning electron microscopy (SEM) investigation combined with energy dispersive (EDS) elemental analysis indicates that traces of K are uniformly distributed in the calcite mass and some S traces for springs 3 and 11 are distributed predominantly into the pseudo-dolomite crystals. The crystalline germs precipitate from the supersaturated solution via homogeneous germination and progressively grow. The latest stage is characterized by the formation of a dendritic crust of calcite mixed with halite that embeds the individually grown crystals. The amount of the formed crystals strongly depends on the water’s total dissolved solids (TDS) and salinity: the springs with high TDS and salinity form a large number of crystals and spectacular dendritic crusts such as spring 10 followed by springs 6 and 5. Lower mineralization was observed in springs 3 and 5, which was related with the S traces. Also, it is evident that mineralization is seasonally dependent: the mineral amount was lower in November 2023 than for the samples collected in March 2024. The obtained mineral powder might be used for spa baths or for the electrolytic balance regulation in dietary supplements due to the high calcium and magnesium content.